Utilization of E-Health Technology in Optimizing Health Services to Increase Patient Satisfaction - Kelegama, Thamali; Ona, Ronald Edilberto; Abdullahi, Mohammad Reza (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study aims to explore the utilization of e-health technology in health service delivery and its impact on patient satisfaction through a comprehensive and contextual qualitative approach. Methodology: The approach used in this study is a qualitative approach with the aim of providing a comprehensive and in-depth picture of e-Health-based Health Service Innovation in Increasing Public Satisfaction at Community Health Centers. Main Findings: This study shows that e-health utilization is influenced by the type of service, age, and digital literacy. Online registration is the most preferred, while other features are less understood. Patient experiences include efficiency, digital literacy barriers, technical constraints, and satisfaction that vary. The main influencing factors are age, access to technology, health worker attitudes, and application design. Health workers play a key role in facilitating the digital transition, with patients expecting a simpler, more inclusive, and trained system. Novelty/Originality of this study: This study offers new insights into how digital literacy, patient context, and health worker support affect the acceptance and effectiveness of e-health services. It contributes to knowledge by highlighting the importance of user-centered implementation and the role of health professionals in facilitating digital transitions in healthcare.